ATRT-04. Clinical and (epi)genetic characterisation of patients with atypical teratoid/rhabdoid tumor (ATRT) and extracranial malignant rhabdoid tumor conceived following assisted reproduction technologies (ART). (3rd June 2022) - Nemes, Karolina; Benesch, Martin; Kolerova, Julia; Johann, Pascal; Hasselblatt, Martin; Thomas, Christian; Bens, Susanne; Liaugaudiene, Olga; Sadeghipour, Alireza; von der Weid, Nicolas; Schmid, Irene; Gidding, Corrie; et al.
Abstract: INTRODUCTION: Anecdotal case reports suggest an association between assisted reproduction technologies (ART) and malignant rhabdoid tumors (MRT). We performed a multi-institutional retrospective analysis of the EU-RHAB database, complemented by additional cases outside of EU-RHAB to compile clinical, (epi)genetic characteristics and outcome data of children with MRT following ART. METHODS: Data of 14 patients (from 311 patients with MRT) from 9 countries were analyzed (2010-2018). Tumors and matching blood samples were examined for SMARCB1 mutations using FISH, MLPA and sequencing. Molecular subgroups were determined using DNA methylation arrays and correlated with a validation cohort (n=22, tumor samples of MRT; n=39 blood samples of patients small for gestational age). RESULTS: The median age at diagnosis of the 13 girls and 1 boy was 9 months (0 – 66). 8 patients with ATRT, 3 with extracranial, extrarenal-, 1 with renal rhabdoid tumor and 2 with synchronous tumors were identified. Distant metastases at diagnosis were present in 6 patients. A germline mutation (GLM) was detected in 5 patients. In 11 tumors complete data on SMARCB1 mutational status were available. DNA methylation subgrouping was available in 10 tumors and 6 blood samples. A female predominance was noted as compared to the EU-RHAB cohort with MRT born without ART (n=213, p=0.009). A total of 8 patients received gross total resection, n=12 patients received conventional chemotherapy (EU-RHAB=9, Head Start II=2, IRS III=1). Radiotherapy was applied to 6 patients. 10 patients achieved CR, and 5 remain in continuing CR. Significant genome-wide DNA methylation differences (including imprinted genes) between patients born after ART and patients born without ART could not be demonstrated. CONCLUSIONS: Long-term survival is achievable in patients who develop MRT after ART, even in cases with GLM, metastatic disease at diagnosis, or relapse. Larger epidemiological studies are needed to confirm a potential association between MRT and ART.